Selective Binding of Heparin/Heparan Sulfate Oligosaccharides to Factor H and Factor H-Related Proteins: Therapeutic Potential for C3 Glomerulopathies - Loeven, Markus A.; Maciej-Hulme, Marissa L.; Yanginlar, Cansu; Hubers, Melanie C.; Kellenbach, Edwin; de Graaf, Mark; van Kuppevelt, Toin H.; Wetzels, Jack; Rabelink, Ton J.; Smith, Richard J. H.; van der Vlag, Johan (Frontiers in Immunology, 2021)
Complement dysregulation is characteristic of the renal diseases atypical hemolytic uremic syndrome (aHUS) and complement component 3 glomerulopathy (C3G). Complement regulatory protein Factor H (FH) inhibits complement activity, whereas FH-related proteins (FHRs) lack a complement regulatory domain. FH and FHRs compete for binding to host cell glycans, in particular heparan sulfates (HS). HS is a glycosaminoglycan with an immense structural variability, where distinct sulfation patterns mediate specific binding of proteins. Mutations in FH, FHRs, or an altered glomerular HS structure may disturb the FH:FHRs balance on glomerular endothelial cells, thereby leading to complement activation and the subsequent development of aHUS/C3G. In this study, we aimed to identify specific HS structures that could specifically compete off FHRs from HS glycocalyx (HSGlx), without interfering with FH binding. FH/FHR binding to human glomerular endothelial cells (ciGEnCs) and HSGlx purified from ciGEnC glycocalyx was assessed. HS modifications important for FH/FHR binding to HSGlx were analyzed using selectively desulfated heparins in competition with purified HSGlx. We further assessed effects of heparinoids on FHR1- and FHR5-mediated C3b deposition on ciGEnCs. In the presence of C3b, binding of FH, FHR1 and FHR5 to ciGEnCs was significantly increased, whereas binding of FHR2 was minimal. FHR1 and 5 competitively inhibited FH binding to HSGlx, leading to alternative pathway dysregulation. FHR1 and FHR5 binding was primarily mediated by N-sulfation while FH binding depended on N-, 2-O- and 6-O-sulfation. Addition of 2-O-desulfated heparin significantly reduced FHR1- and FHR5-mediated C3b deposition on ciGEnCs. We identify 2-O-desulfated heparin derivatives as potential therapeutics for C3G and other diseases with dysregulated complement.